Radiological Contamination: A Modern Overview (Eurasian Research Bulletin, 2026)
Radiological contamination of the environment remains one of the most pressing contemporary challenges, arising from both natural sources of ionizing radiation and anthropogenic activities. This comprehensive review presents a systematic analysis of current scientific data on the sources of radioactive contamination, mechanisms of biological impact on the human body, epidemiology of radiation-induced diseases, and contemporary approaches to diagnosis, treatment, and prevention of radiation injuries. Based on authoritative international sources — including epidemiological studies of the Japanese atomic bombings, the Chernobyl and Fukushima accidents, as well as long-term observations of occupational and medical exposed cohorts — the review examines current concepts of stochastic and deterministic effects of ionizing radiation. Particular attention is paid to the analysis of the radiation situation in the Russian Federation in 2024, including the structure of radiation accidents, the problem of unauthorized circulation of radioactive sources, and contamination of food products. The article is intended for specialists in radiation hygiene, ecology, disaster medicine, and for a broader audience interested in radiation safety issues